Comparative Environmental Sustainability of Reusable SUNS Proque Versus Level 3 PPE in COVID-19 Isolation Wards - Dony Marthen Bani; Darmawan Ismail; Suwardi; Ida Bagus Budhi Surya Adhnyana; Wibisono; Pigur Agus Marwanto (Health and Medical Journal, 2026)
Background: The COVID-19 pandemic led to an unprecedented surge in the use of disposable personal protective equipment (PPE), contributing to a substantial increase in medical waste and environmental pollution. While Level 3 disposable PPE is widely used to protect healthcare workers, its environmental sustainability remains a growing concern. Reusable PPE systems, such as the Surgeons of Universitas Sebelas Maret Protective Equipment (SUNS Proque), have been developed as alternatives to mitigate environmental impacts while maintaining adequate protection. Objective: This study aimed to compare the environmental sustainability of reusable SUNS Proque PPE and conventional Level 3 disposable PPE used in COVID-19 isolation wards. Methods: An observational analytical cross-sectional study was conducted at Dr Moewardi Hospital in Indonesia. A total of 56 healthcare workers (physicians, nurses, and sanitation staff) who had experience using both PPE types participated. Environmental sustainability was assessed using a validated 10-item Likert-scale questionnaire covering recyclability, reusability, waste volume, material characteristics, waste segregation, and circular economy principles. Statistical analyses included Chi-square tests, independent t-tests, and Eta correlation analysis. Results: SUNS Proque PPE demonstrated significantly higher overall environmental sustainability compared with Level 3 PPE (p < 0.001). Significant differences were observed in recyclability (p = 0.025), design for reuse (p = 0.002), waste volume reduction (p = 0.017; Eta = 0.772), and waste segregation (p = 0.013). Waste volume emerged as the strongest determinant differentiating the two PPE systems. Other indicators, including material toxicity and non-incineration processing, showed no statistically significant differences. Conclusion: Reusable SUNS Proque PPE offers superior environmental sustainability compared with conventional disposable Level 3 PPE, particularly through substantial waste reduction. Integrating reusable PPE into hospital infection control strategies may support environmentally sustainable healthcare systems without compromising occupational safety.